Social Innovation: Examples within Hungarian context (ENTRENOVA - ENTerprise REsearch InNOVAtion Journal, 2020)
There are many definitions of social innovation, out of which the most commonly accepted may be that it is a complex solution or, sometimes disruptive, change that is more efficient, effective, sustainable and fair than existing alternatives on the broadest level of society. A further, essential characteristic of it is a community framework, manifested in the creation of new relationships and the restructuring of the entrenched modes of cooperation. Adding to the significance of the phenomenon is that nowadays every social challenge is deemed an economic one as well. Hence, its solution is in the interest of the national economy. The most important sectors and challenges: demography, poverty, climate change, education, digitalization, public administration, health care. Some highlighted recent examples of social innovation are the following: social enterprise, creating shared value (CSV), emissions trading, fair trade and social webshops. The goal of the paper is to interpret social innovation as widely as possible through individual examples within Hungarian context.This work is licensed under a Creative Commons Attribution-NonCommercial 4.0 International License.